First Food Policy and Law Scan: How Tribes in the Bemidji Area Are Applying Policy and Systems Approaches to Support Breastfeeding - Aoki, Julie Ralston (Prev Chronic Dis, 2021)
The objective of the First Food Policy and Law Scan was to identify breastfeeding policies adopted by federally recognized Tribes in the Indian Health Service’s Bemidji Area to understand how breastfeeding is supported through policy. In 2018–2019, we invited all federally recognized Tribes in the Bemidji Area (Michigan, Minnesota, and Wisconsin) to share information on policies in 6 settings (eg, government, casinos). Tribal contacts shared 61 policies from 31 Tribes. We analyzed the policies for 17 features. The project demonstrated that one way the Bemidji Area Tribal Nations are addressing chronic diseases is by applying policy to support breastfeeding.